2013
DOI: 10.1007/s11999-012-2352-1
|View full text |Cite
|
Sign up to set email alerts
|

Is Administratively Coded Comorbidity and Complication Data in Total Joint Arthroplasty Valid?

Abstract: The data suggest administratively coded comorbidities and complications correlate reasonably well with the clinical record. However, the specificity of administrative claims is much higher than the sensitivity, indicating that comorbidities and complications coded in the administrative record were accurate but often incomplete.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
99
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 160 publications
(101 citation statements)
references
References 11 publications
1
99
0
1
Order By: Relevance
“…First, we relied on administrative claims data (which did not include laterality) to identify revisions and risk factors for early failure. However, previous investigators have reported reasonable correlation between administrative claims and the clinical record when evaluating causes and types of revision TJA procedures [2]. Second, our study was limited to Medicare patients, and therefore our findings may not be generalizable to the broader population of younger patients who undergo primary THA.…”
Section: Discussionmentioning
confidence: 83%
“…First, we relied on administrative claims data (which did not include laterality) to identify revisions and risk factors for early failure. However, previous investigators have reported reasonable correlation between administrative claims and the clinical record when evaluating causes and types of revision TJA procedures [2]. Second, our study was limited to Medicare patients, and therefore our findings may not be generalizable to the broader population of younger patients who undergo primary THA.…”
Section: Discussionmentioning
confidence: 83%
“…First, as in all claims-based studies, coding misclassification can occur. It has been shown that administrative data tend to have high specificity (that is, a low false-positive rate) but low sensitivity (a high falsenegative rate) in identifying comorbidities and complications [11,22]. Thus, if anything, our data source underestimates the prevalence of opioid abuse and dependence.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies have found administrative claims to be useful in orthopaedic surgery [14,24], and specifically in THA [3][4][5]. Bozic et al [2] compared administrative claims data with institutional data and reported that it was highly specific ([ 92%) for each arthroplasty-relevant complication and comorbidity tested but variable in their sensitivity (29%-100%). This level of accuracy may be sufficient for this study but also could influence the results, especially if documentation was more thorough for revisions of one bearing surface type compared with the other.…”
Section: Discussionmentioning
confidence: 99%
“…This searchable database contains 100% of both inpatient and outpatient claims with more than 50 million unique patient records including 1.1 million THAs. This research tool has been used in various studies in orthopaedic surgery [14,24] and has been specifically validated for complications after total joint arthroplasty [2].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation